Influence of bone marrow on osseointegration in long bones: an experimental study in sheep - Morelli, Fabrizio; Lang, Niklaus P.; Bengazi, Franco; Baffone, Davide; Dadonim Vila Morales, C.; Botticelli, Daniele [UNESP] (Wiley-Blackwell, 2015)
Aim To evaluate the influence of yellow bone marrow on osseointegration of titanium oral implants using a long bone model.Material and methodsThe two tibiae of eight sheep were used as experimental sites. Two osteotomies for implant installation were prepared in each tibia. At the control sites, no further treatments were performed while, at the test sites, bone marrow was removed from the osteotomy site with a curette to an extent that exceeded the implant dimensions. As a result, the apical portion of the implants at the control sites was in contact with bone marrow while, at the test sites, it was in contact with the blood clot. After 2months, the same procedures were performed in the contralateral side. After another month, the animal was sacrificed. Ground sections were obtained for histological analysis.ResultsAfter 1month of healing, no differences between test and control sites were found in the apical extension of osseointegration and the percentage of new bone-to-implant contact. However, after 3months of healing, a higher percentage of new bone-to-implant contact was found at the test compared to the control sites in the marrow compartment. The apical extension of osseointegration, however, was similar to that found at the 1-month healing period both for test and control sites.ConclusionsOsseointegration appeared to be favored by the presence of a blood clot when compared to the presence of yellow fatty bone marrow. Moreover, the contact with cortical bone appeared to be a prerequisite for the osseointegration process in the long bone model.
Keywords: Animal study; Bone formation; Bone marrow; Implant dentistry; Long bones; Osseointegration